LAK21: 11th International Learning Analytics and Knowledge Conference 2021
DOI: 10.1145/3448139.3448179
|View full text |Cite
|
Sign up to set email alerts
|

Quantum of Choice: How learners’ feedback monitoring decisions, goals and self-regulated learning skills are related

Abstract: Learning analytics dashboards (LADs) are designed as feedback tools for learners, but until recently, learners rarely have had a say in how LADs are designed and what information they receive through LADs. To overcome this shortcoming, we have developed a customisable LAD for Coursera MOOCs on which learners can set goals and choose indicators to monitor. Following a mixedmethods approach, we analyse 401 learners' indicator selection behaviour in order to understand the decisions they make on the LAD and wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 38 publications
1
24
0
2
Order By: Relevance
“…Further investigations into the details of the log data from Moodle revealed that these engagement behaviours mainly focused on sharing individual reflections and asking questions to teachers. This particularly links to the recent findings from Jivet et al [35] that only the high SRL skills, specifically high help-seeking skills will value the discussion forum as a sort of help. It was also observed that students with high SRL competence have a higher frequency of viewing others' reflection input as well as viewing discussions between students and teachers.…”
Section: Discussionsupporting
confidence: 65%
“…Further investigations into the details of the log data from Moodle revealed that these engagement behaviours mainly focused on sharing individual reflections and asking questions to teachers. This particularly links to the recent findings from Jivet et al [35] that only the high SRL skills, specifically high help-seeking skills will value the discussion forum as a sort of help. It was also observed that students with high SRL competence have a higher frequency of viewing others' reflection input as well as viewing discussions between students and teachers.…”
Section: Discussionsupporting
confidence: 65%
“…We conducted comprehensive searches on Scopus (390 documents) and Web of Science (164 documents) in May 2022. Additionally, we used Google Scholar to search for records published by the Journal of Learning Analytics (142), the Journal of Educational Data Mining (35), and the International Conference on Educational Data Mining (22). The Journal of Learning Analytics, Journal of Educational Data Mining, and International Conference of Educational Data Mining are not fully indexed in the Scopus or Web of Science databases.…”
Section: Methodsmentioning
confidence: 99%
“…Examples of such product data are the outcomes of formative assessments or diagnostic entry tests. In applications of DLA, a third data source is provided by the self-report surveys applied to measure learning dispositions; although attempts are being made to measure dispositions through the observation of learning behaviors (Buckingham Shum and Deakin Crick, 2016;Cloude et al, 2020;Jivet et al, 2021;Salehian Kia et al, 2021), the survey method is still dominant (Shum and Crick, 2012).…”
Section: Personalized Learning and Multi-modal Data Sourcesmentioning
confidence: 99%
“…In Dispositional Learning Analytics (DLA) researchers aim to complement trace data with other subjective (e.g., survey data) and/or objective (e.g., continuous engagement proxies) measures of learners' orientation to learning. Recently several attempts are being made to identify behavioral proxies of learning dispositions that are trace-based (Connected Intelligence Centre, 2015;Buckingham Shum and Deakin Crick, 2016;Jivet et al, 2021;Salehian Kia et al, 2021). For example, in a study of 401 MOOC learners, Jivet et al (2021) allowed participants to select a learning analytics dashboard that matched with their respective phase of self-regulated learning (SRL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation